Joint effects of cancer and variants in the factor 5 gene on the risk of venous thromboembolism - Gran, Olga Vikhammer; Smith, Erin N.; Brækkan, Sigrid Kufaas; Jensvoll, Hilde; Solomon, Terry; Hindberg, Kristian; Wilsgaard, Tom; Rosendaal, Frits Richard; Frazer, Kelly A.; Hansen, John-Bjarne (Haematologica, 2016)
Source: doi:10.3324/haematol.2016.147405 Venous thromboembolism occurs frequently in cancer patients. Two variants in the factor 5 gene (F5), rs6025 encoding for the factor V Leiden mutation R506Q, and rs4524 encoding K858R, have been found to be associated with venous thromboembolism. We assessed the joint effect of active cancer and these two F5 variants on venous thromboembolism risk in a case-cohort study. Cases with a first venous thromboembolism (n=609) and a randomly selected age-weighted cohort (n=1,691) were sampled from the general population in Tromsø, Norway. Venous thromboembolism was classified as cancer-related if it occurred in the period 6 months before to 2 years after a diagnosis of cancer. Active cancer was associated with an 8.9-fold higher risk of venous thromboembolism (95% CI 7.2–10.9). The risk of cancer-related venous thromboembolism was 16.7-fold (95% CI 9.9–28.0) higher in subjects heterozygous for rs6025 compared with non-carriers of this variant without active cancer. In subjects with active cancer the risk of venous thromboembolism was 15.9-fold higher (95% CI 9.1–27.9) in those with one risk allele at rs4524, and 21.1-fold (95% CI 12.4–35.8) higher in those with two risk alleles compared with non-carriers without active cancer. A synergistic interaction was observed between active cancer and factor V Leiden (relative excess risk due to interaction 7.0; 95% CI 0.5–14.4) and rs4524 (relative excess risk due to interaction 15.0; 95% CI 7.5–29.2). The incidence of venous thromboembolism during the initial 6 months following a diagnosis of cancer was particularly high in subjects with risk alleles at these loci. This implies that the combination of cancer and F5 variants synergistically increases venous thromboembolism risk.